Influence of Operating Conditions on Pre-wetted Powder Explosion - Olivier Dufaud; Enrico Danzi; Luca Marmo (Chemical Engineering Transactions)
Pre-wetting of powders or wet granulation are commonly used in industrial processes and the presence of a flammable liquid compound can affect the ignition sensitivity and explosion severity of such admixtures. This study shows that for risk assessment, it is not possible to consider this type of admixture to be equivalent to a hybrid gas/solid mixture of the same composition. Indeed, if the introduction of a solvent tends to increase the explosion risk, pre-wetting also significantly modifies the particle size distribution of the admixture, which counterbalances the positive contribution of the flammable liquid. Dispersing the dust requires then a greater dispersion pressure to reach the same surface area between solid fuel and oxidizer. In the case of the determination of the minimum ignition temperature, such changes lead to a modification of the optimal operating conditions. It should also be noted that the fuel equivalence ratio is a good indicator for assessing the chemical contribution of such admixtures.